Thermoluminescence characteristics of flat optical fiber in radiation dosimetry under different electron irradiation conditions - Alawiah, A.; Intan, A.M.; Bauk, S.; Abdul-Rashid, H.A.; Yusoff, Z.; Mokhtar, M.R.; Wan Abdullah, W.S.; Mat Sharif, K.A.; Mahdiraji, G.A.; Adikan, Faisal Rafiq Mahamd; Tamchek, N.; Noor, N.M.; et al. (International Society for Optical Engineering, 2013)
Thermoluminescence (TL) flat optical fibers (FF) have been proposed as radiation sensor in medical dosimetry for both diagnostic and radiotherapy applications. A flat optical fiber with nominal dimensions of (3.226 × 3.417 × 0.980) mm3 contains pure silica SiO2 was selected for this research. The FF was annealed at 400°C for 1 h before irradiated. Kinetic parameters and dosimetric glow curve of TL response were studied in FF with respect to electron irradiation of 6 MeV, 15 MeV and 21 MeV using linear accelerator (LINAC) in the dose range of 2.0-10.0 Gy. The TL response was read using a TLD reader Harshaw Model 3500. The Time-Temperature-Profile (TTP) of the reader used includes; initial preheat temperature of 80°C, maximum readout temperature is 400°C and the heating rate of 30°Cs-1. The proposed FF shows excellent linear radiation response behavior within the clinical relevant dose range for all of these energies, good reproducibility, independence of radiation energy, independence of dose rate and exhibits a very low thermal fading. From these results, the proposed FF can be used as radiation dosimeter and favorably compares with the widely used of LiF:MgTi dosimeter in medical radiotherapy application. © (2013) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.